Effectiveness of Sexual and Reproductive Health Education Interventions among Adolescents: A Systematic Review - Izattul Azijah; Yuna Trisuci Aprillia; Asyifa Robiatul Adawiyah (Science Tech Group, 2026)
Background: Adolescents remain vulnerable to adverse sexual and reproductive health (SRH) outcomes, including unintended pregnancy, sexually transmitted infections (STIs), HIV exposure, unsafe abortion, and limited access to youth-friendly services. Comprehensive sexuality education is recommended as a core public health strategy to improve knowledge, attitudes, skills, and protective behaviors. Objective: This systematic review synthesized intervention evidence on the effectiveness of SRH education among adolescents and young adults. Methods: The review followed PRISMA 2020 guidance. Scopus, PubMed, and Dimensions were searched for English-language studies published from 2016 to 2025. Eligible studies included adolescents or young adults exposed to school- or community-based SRH education interventions and reported measurable knowledge, attitudinal, self-efficacy, service use, or behavioral outcomes. The risk of bias was assessed using the Cochrane RoB 2 tool. Due to heterogeneity in interventions and outcome measures, findings were synthesized narratively. Results: From 394 records, 18 duplicates were removed, and 376 records were screened. Five full-text reports were assessed, two were excluded after methodological appraisal, and three studies were included. The included studies were conducted in Colombia, India, and Liberia and collectively showed positive effects of SRH education on reproductive-health knowledge, HIV/STI knowledge, self-efficacy, condom-related attitudes, contraceptive use, condom use, and HIV testing. Participatory approaches, including group discussion, peer learning, role-play, and service-linked education, appeared particularly promising. Conclusion: SRH education interventions can improve adolescents' SRH knowledge and selected protective behaviors, especially when interactive, culturally responsive, and linked to accessible services. However, the small number of included studies, self-reported outcomes, and heterogeneity of measures limit certainty. Future trials should use standardized outcomes, longer follow-up periods, implementation fidelity assessment, and equity-sensitive analyses.